Pengembangan Alat Pelontar Bola Sepak Untuk Melatih Keterampilan Penjaga Gawang - Saputra , Randyka Cahya Saputra; Putro , Danang Endarto; Astuti , Ridha Kurniasih (JSH: Journal of Sport and Health, 2025)
The aim of this research is to develop a soccer ball throwing device that can be used to train goalkeeper skills in the sport of soccer. The research employs a development method (Research and Development/R&D), consisting of several stages: (1) Potential and Problems, (2) Information Collection, (3) Product Design, (4) Product Validation, (5) Design Improvement, (6) Product Testing, (7) Product Revision, (8) Product Testing, (9) Product Revision, and (10) Final Product. The instruments used in this study include observation, interviews, questionnaires, and documentation. Product validation was conducted by material and media experts. Data analysis was performed using the Likert scale.The results of the research showed: (1) material expert validation data scored 46 (92%), categorized as "Very Good," (2) med ia expert validation scored 50 (100%), categorized as "Very Good." In the small-scale trial, 22 players from Tidar Jaya and PSS Sukoharjo achieved an average score of 83%, categorized as "Very Good," while the large-scale trial with 44 players also achieved an average score of 83%, categorized as "Very Good." Based on these results, the soccer ball throwing device was proven effective in training goalkeeper skills and is suitable for use in soccer training.